Evaluation of pulsed laser deposited thin films properties on the basis of the nanoindentation test. (2017) - Perzyński, Konrad; Cios, Grzegorz; Szwachta, Grzegorz; Zych, Dawid; Setty, Mohan; Bała, Piotr; Madej, Łukasz
Abstract: The overall goal of the research, is development of the numerical model capable of replicating local heterogenous material behavior of thin film materials under loading conditions. This particular work is focused on determination of flow stress characteristics of investigated TiN thin film based on the nanoindentation test. To properly recalculate measured load-displacement values into the required stress-strain curve an inverse analysis techniques are used. Subsequent stages including deposition process of TiN layer, room temperature nanoindentation tests and development of direct problem numerical model for the inverse analysis are described. Capabilities of the approach are also discussed within the work.